Origin and genetic diversity of Nepalese indigenous goats (Capra hircus) - Gorkhali, N.A.; Lin, J.; Sapkota, Suraj; Pokhrel, B.R.; Ma, Y.H.; Han Jianlin (Agricultural Research Communication Center, 2021)
Background: A very little study has been conducted on the phylogenetic diversity of Nepalese indigenous goats where four breeds, Khari, Chyangra, Terai and Sinhal, have been identified. Methods: The 625-bp long sequences of the mitochondrial DNA hyper-variable region obtained from 93 goats in this study revealed high haplotype diversity among breeds, which come under four haplogroups (A-D).Result: The study demonstrated a certain level of gene flow among the neighboring goat populations exhibiting no correspondence between the geographic regions of origin and relationships among breeds. The complex mtDNA diversity and structure identified among indigenous Nepalese goats can be explained by gene flow through ancient trading and the current ‘free’ movement of goats across the geographic vicinities in India and China. Furthermore, HapG B showed the southward direction of gene flow which does not cross the Himalayas, whereas HapG B1 revealed the South-West gene flow from the claimed domestication center for HapG B, China, to Nepal.